Optimization of phototrophic hydrogen production by Rhodopseudomonas palustris PBUM001 via statistical experimental design - Jamil, Z.; Mohamad Annuar, M.S.; Ibrahim, S.; Vikineswary, S. (2009)
Phototrophic hydrogen production by indigenous purple non-sulfur bacteria, Rhodopseudomonas palustris PBUM001 from palm oil mill effluent (POME) was optimized using response surface methodology (RSM). The process parameters studied include inoculum sizes ( v/v), POME concentration ( v/v), light intensity (klux), agitation (rpm) and pH. The experimental data on cumulative hydrogen production and COD reduction were fitted into a quadratic polynomial model using response surface regression analysis. The path to optimal process conditions was determined by analyzing response surface three-dimensional surface plot and contour plot. Statistical analysis on experimental data collected following Box-Behnken design showed that 100 (v/v) POME concentration, 10 (v/v) inoculum size, light intensity at 4.0 klux, agitation rate at 250 rpm and pH of 6 were the best conditions. The maximum predicted cumulative hydrogen production and COD reduction obtained under these conditions was 1.05 ml H2/ml POME and 31.71 respectively. Subsequent verification experiments at optimal process values gave the maximum yield of cumulative hydrogen at 0.66 ± 0.07 ml H2/ml POME and COD reduction at 30.54 ± 9.85. © 2009 International Association for Hydrogen Energy.